Capstone Programming Courses Considered Harmful. - WRIGHT, KEITH (Communications of the ACM, 2010)
The article presents the author's opinion on the decline in computer-related degree programs as well as the decline in demand for U.S. programmers. The loss of student interest in computer sciences is examined. The author's experiences working with several Fortune 500 companies as a computer programmer including for Informatics, Information Engineering systems Corporation, and International Business Machines are explored. How to redesign computer curricula to address economic needs such as replacing capstone or senior programming courses with internships that emphasize ethical IT service-level management is discussed.